Evaluation of the sensitivity and production of flowers in Tagetes erecta L. exposed to high doses of sodium from irrigation with landfill leachates - M.G. Abrile; M.L. Fiasconaro; S. Gervasio; M.C. Antolín; M.E. Lovato (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Reuse of landfill leachate is an effective alternative for their nutrients to mitigate decrease in freshwater. On the other hand, the growth of vegetation in the final disposal areas provides many benefits such as improving the visual impact, controlling of hydric erosion, etc. The purpose of this work was to evaluate landfill leachate as irrigation water and source of nutrients for growth of Tagetes erecta L., an ornamental plant with phytoremediation capacities. Method Vegetal growth, physiological responses and mineral elements uptake of the ornamental plant Tagetes erecta L. were studied with different levels of landfill leachate irrigation. The landfill leachate was provided by the municipal waste treatment. Experimental period covered 34 days of daily watering between the beginning and end of the flowering stage. Three different irrigation treatments were used: T1: 10% leachate; T2: 25% leachate; T3: 50% leachate. Hoagland's solution served as the control treatment. Results The irrigation treatment with a dose of 50% leachate causes a clear deterioration in the plant and its flowers. In lower doses, the plant responds favorably to both the production of flowers and the main features of them. Also, the water-use efficiency (WUE) is diminished in those plants irrigated with the major dose of leachate. Conclusion Maintaining controlled doses, landfill leachates can be used as an alternative source of water and nutrients. Irrigation with leachates of these characteristics should be done in dosages not higher than 25% to avoid possible damage of Tagetes erecta L. growth.